Creativity, Inc overcoming the unseen forces that stand in the way of true inspiration - Catmull, Edwin E. (New York Random House Audio, 2014)
Creativity, Inc. is a book for managers who want to lead their employees to new heights, a manual for anyone who strives for originality, and the first-ever, all-access trip into the nerve center of Pixar Animation--into the meetings, postmortems, and 'Braintrust' sessions where some of the most successful films in history are made. It is, at heart, a book about how to build a creative culture--but it is also, as Pixar co-founder and president Ed Catmull writes, 'an expression of the ideas that I believe make the best in us possible
Keywords: Creative ability in business